Clinical Manifestations, Neuroimaging Findings, and Treatment of Idiopathic Intracranial Hypertension in a Nepalese Tertiary Centre - Gautam, Niraj; Ojha, Rajeev; Kharel, Sanjeev; Gajurel, Bikram Prasad; Sitaula, Sanjeeta; Karn, Ragesh; Rajbhandari, Reema; Shrestha, Ashish (Nepalese Medical Journal, 2021)
Introduction: Idiopathic Intracranial Hypertension is characterized by headache, visual impairment, papilledema, and increased cerebrospinal fluid opening pressure. We aim to evaluate clinical manifestations, neuroimaging findings, and treatment of Idiopathic Intracranial Hypertension in a Nepalese tertiary center. Materials and Methods: We retrospectively included patients with the diagnosis of Idiopathic Intracranial Hypertension who were admitted to the Neurology department of Tribhuvan University Teaching Hospital from 2019 June to 2021 May and presented to the Neuro-ophthalmology outpatient clinic of the hospital for follow-up. Results: Out of 16 Idiopathic Intracranial Hypertension patients, 12(75%) patients had either headache or ocular pain. Reduced visual acuity and progressive visual loss were found in 44% of patients. Normal CSF opening pressure was found in 19%, 44% had CSF opening pressure at a range of 20-30 cm H20 and > 30 cm H20 in 37.5%. 15 Idiopathic Intracranial Hypertension patients (93.7%) were subtyped as Typical and 1 patient was diagnosed as Fulminant Idiopathic Intracranial Hypertension. Acetazolamide was used for treatment in 15 patients and 1 patient needed ventriculoperitoneal shunting. 56% Seven patients (44%) had some abnormal findings: partial empty sella (44%), and tortuous optic nerve (31%), flattened posterior eyeball (31%), and hypoplastic transverse sinus (19%). Conclusions: Idiopathic Intracranial Hypertension is an uncommon diagnosis but should be suspected in patients with chronic headaches with visual impairment. In low-resource settings, proper history along with neurological and ophthalmological examinations can even detect the early features and timely referral can save the vision and disability of Idiopathic Intracranial Hypertension patients.